Temporality and the evocation of fear and unease in selected video installations - Driscoll, Patricia (My University, 2014)
In this research I explore the evocation of fear and unease in selected video installations and how time impacts upon such evocation. For this purpose I consider the works of selected contemporary artists who deal directly with a form of time-‐based hyper-‐awareness linked to the experience of trauma, fear and panic. Amongst others, I discuss selected video artworks by Douglas Gordon, Ed Atkins, and South African artists William Kentridge, Kendell Geers and Berni Searle. I examine how such artworks engage with the expansion and collapse of time and experiences of being stuck or being absorbed in a significant moment. In undertaking this research I closely examine the mediums of film and video as well as contexts and the installation formats in which they are presented. I explore similar aspects of evoking unease in my own video installation titled Night-light and the supporting video work submitted for this degree. My previous creative experience has been in still photography in which I had become interested in exploring the capturing of time and movement and imparting an immersive temporal dimension or an extended moment in time in the still image. I see my exploration of the medium of video installation for the MA submission as an extension of such explorations in a new medium through which I further explore the concern with a temporal dynamic and its relationship to the emotion and experience of (personal) unease.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities and Social Sciences, Fine Arts, 2013